German guideline diverticular disease/diverticulitis: Part I: Methods, pathogenesis, epidemiology, clinical characteristics (definitions), natural course, diagnosis and classification. Issue 9 (21st November 2022) - Kruis, Wolfgang; Germer, Christoph‐Thomas; Böhm, Stephan; Dumoulin, Franz L.; Frieling, Thomas; Hampe, Jochen; Keller, Jutta; Kreis, Martin E.; Meining, Alexander; Labenz, Joachim; Lock, Johann F.; Ritz, Jörg P.; et al.
Abstract: Diverticulosis and diverticular disease are ranked among the most common gastroenterological diseases and conditions. While for many years diverticulitis was found to be mainly an event occurring in the elder population, more recent work in epidemiology demonstrates increasing frequency in younger subjects. In addition, there is a noticeable trend towards more complicated disease. This may explain the significant increase in hospitalisations observed in recent years. It is not a surprise that the number of scientific studies addressing the clinical and socioeconomic consequences in the field is increasing. As a result, diagnosis and conservative as well as surgical management have changed in recent years. Diverticulosis, diverticular disease and diverticulitis are a complex entity and apparently an interdisciplinary challenge. To meet theses considerations the German Societies for Gastroenterology and Visceral Surgery decided to create joint guidelines addressing all aspects in a truely interdisciplinary fashion. The aim of the guideline is to summarise and to evaluate the current state of knowledge on diverticulosis and diverticular disease and to develop statements as well as recommendations to all physicians involved in the management of patients with diverticular disease.